Analisis Pengaruh Pengalaman Terhadap Kompetensi Serta Pengaruhnya Terhadap Produktivitas Ukm Di Kota Denpasar, Provinsi Bali - I Wayan Chandra Adyatma; Desak Rurik Pradnya Paramitha Nida (Lembaga Penelitian, Universitas Warmadewa, 2021)
This study aims to see the effect of work experience on competence, as well as the effect on the productivity of SMEs in Denpasar City. The analysis used in this study is to use path analysis with a one-way model. The data used in this study are primary data shown to SME actors and employees in Denpasar City, a questionnaire that can be entered into 100 questionnaires. From the results of the calculation of the analysis test carried out by the researcher, the calculation of the results provides an overview: (1) the work experience variable shows a significant and positive influence on the productivity of the actors (owners and employees) of SMEs in Denpasar City. (2) the compensation variable shows a significant and positive influence on the productivity of employees and owners of UKM in Denpasar City. (3) the work experience variable shows a significant and positive influence on the competency variables of SMEs in Denpasar City, Bali Province.